The Salinity Signature of the Cross-Shelf Exchanges in the Southwestern Atlantic Ocean: Numerical Simulations - Matano, Ricardo (2014)
A high-resolution model is used to characterize the dominant patterns of sea surface salinity (SSS) variability generated by the freshwater discharges of the Rio de la Plata (RdlP) and the Patos/Mirim Lagoon in the southwestern Atlantic region. We identify three dominant modes of SSS variability. The first two, which have been discussed in previous studies, represent the seasonal variations of the freshwater plumes over the continental shelf. The third mode of SSS variability, which has not been discussed hitherto, represents the salinity exchanges between the shelf and the deep ocean. A diagnostic study using floats and passive tracers identifies the pathways taken by the freshwater plumes. During the austral winter (JJA) the plumes leave the shelf region north of the BMC. During the austral summer (DJF), the plumes are entrained more directly into the BMC. A sensitivity study indicates that the high frequency component of the wind stress forcing controls the vertical structure of the plumes while the low-frequency component of the wind stress forcing and the inter- annual variations of the RdlP discharge controls the horizontal structure of the plumes. Dynamical analysis reveals that the cross-shelf flow has a dominant barotropic structure and, therefore, the SSS anomalies detected by Aquarius represent net mass exchanges between the shelf and the deep ocean. The net cross-shelf volume flux is 1.21 Sv. This outflow is largely compensated by an inflow from the Patagonian shelf.